Análisis del crecimiento urbano de la ciudad de zumba y su efecto sobre los recursos naturales en el período 2010 – 2020 - Urrego Jiménez, María Janeth (2023)
The objective of the research was to evaluate the urban growth of the city of Zumba and its influence on natural resources, specifically soil, water, and vegetation cover. The city has experienced unplanned growth that has led to the loss and alteration of natural resources, mainly due to anthropogenic activities such as agriculture and cattle ranching. Open source Geographic Information Systems (GIS) was used to determine urban growth through a multitemporal analysis and land cover change between the years 2010 and 2020 in the Zumbayacu micro-watershed. In addition, a cause-effect matrix was applied to measure the influence of urban growth on natural resources and to present a proposal aimed at the orderly growth of the city of Zumba. The results of urban growth in the city of Zumba increased by 7.20 ha during the period analyzed. In this period, the surface area of the Zumbayacu micro-watershed cover has decreased, 16.11 % for native forest, 4. 90 % crops and 13.59 % shrub vegetation. According to the cause-effect matrix applied, vegetation cover was the most affected resource with an impact of 19.97%, while the peri-urban area had the greatest negative influence with 19.28% of the total study areas. The proposal oriented to the orderly growth of the city is an important tool to counteract the changes produced within the study area; therefore, agrological class maps are shown as a support tool for its possible application. Keywords: Urban planning - Multi-temporal analysis - Coverage changes - Urban growth